Arqueología en espacios contrastados en los piedemontes oriental y occidental de Cumbres Calchaquíes (Tucumán-Argentina) durante el 1° y 2° milenio de la era - Caria, Mario Alejandro (2015)
This chapter synthetises and discusses archaeological knowledge generated over nearly a decade of work in the eastern and western slopes of the Cumbres Calchaquíes (Tucumán Province, Argentina).Traditionally, archaeologists considered both slopes as partially disconnected halves rather than seeing them as an articulated unit as suggested by pre-Hispanic practices. These spaces, while having highly contrasting environmental characteristics, have maintained over time close ties that justify an integrated approach to their cultural development. In this paper we consider the area of the summits not as a barrier/obstacle, but more as an element that shapes, gives coherence and historical identity to the pre-Hispanic populations related to it. In order to visualize these relationships in historical perspective, investigations aimed at characterizing the spatial process of occupation of the area with a particular focus on first millennium A.D. sites as they can be considered representative of Formative period lifestyles, with marked differences to those observed in earlier and later periods. We offer an explanatory model of the historical processes that unfolded in the area, integrating palaeoenvironmental information, settlement patterns, movement of goods and social relations between the pre-Hispanic groups.